Micro Three-Dimensional Neuronal Cultures Generate Developing Cortex-Like Activity Patterns - Ming, Yixuan; Hasan, Md Fayad; Tatic-Lucic, Svetlana; Berdichevsky, Yevgeny (Frontiers in Neuroscience, 2020)
Studies aimed at neurological drug discovery have been carried out both in vitro and in vivo. In vitro cell culture models have showed potential as drug testing platforms characterized by high throughput, low cost, good reproducibility and ease of handling and observation. However, in vitro neuronal culture models are facing challenges in replicating in-vivo-like activity patterns. This work reports an in-vitro culture technique that is capable of producing micro three-dimensional (µ3D) cultures of only a few tens of neurons. The µ3D cultures generated by this method were uniform in size and density of neurons. These µ3D cultures had complex spontaneous synchronized neuronal activity patterns which were similar to those observed in the developing cortex and in much larger 3D cultures, but not in 2D cultures. Bursts could be reliably evoked by stimulation of single neurons. Synchronized bursts in μ3D cultures were abolished by inhibitors of glutamate receptors, while inhibitors of GABAA receptors had a more complex effect. This pharmacological profile is similar to bursts in neonatal cortex. Since large numbers of reproducible µ3D cultures can be created and observed in parallel, this model of the developing cortex may find applications in high-throughput drug discovery experiments.